IbM PENERAPAN BIOTEKNOLOGI DAN PENGOLAHAN LIMBAH MEDIA TANAM JAMUR MERANG DI KECAMATAN NISAM KABUPATEN ACEH UTARA - Zuriani zuriani; Rosnina Rosnina; Martina Martina (DHARMA RAFLESIA, 2018)
The cultivation of mushroom in Nisam Subdistrict is constrained by several factors, such as the limited ability of biotechnology breeding and cultivation, marketing and capital. After harvesting, planting media left without any further processing. Moreover, partner farmers has obstacles in terms of marketing and capital limitations for business development. Mushroom cultivation activity was doing by a farmer group "Jamur Nismara" and a farmer group "Tani Jamur" had to stop since the end of 2014 as a consequence. Activities devotion aims to revive the activities of mushroom cultivation that has been there with the technique of better management. The goal to be achieved is a group of reliable and independent farmers. Therefore, the farmers should have knowledge and skills about biotechnology of mushroom cultivation starting from breeding, making the ideal kumbung, correct the cultivation process and processing of planting media waste into compost fertilizer which have an economic value. Farmers must have the ability to access information, especially related to marketing. The methods used are counselling and direct implementation / practice by involving all group members. The results are farmers have kumbung and cultivation ability, marketing, and processing waste media. In addition, farmers also have knowledge about nursery technology. Keywords: mushroom, biotechnology, cultivation, waste media planting